Sport elektroniczny i jego medialne interfejsy - Felczak, Mateusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This paper provides an overview of changes on the electronic sports information circuit in the period from 2012 to 2022. The research here focuses on visual components of e-sports events, especially games’ GUIs and interactive elements of the digital platform interfaces that provide technological scaffolding for e-sports broadcasts (such as Twitch). The analysis is conducted from the software studies perspective, with the StarCraft franchise as a chief example of the phenomena assessed in the paper. The findings presented in this study stem from the juxtaposition of divergent modes of interaction between the viewers, players and e-sports media professionals, which are subsequently confronted with the computational rules of e-sports games’ mechanics.